2002
DOI: 10.3748/wjg.v8.i2.217
|View full text |Cite
|
Sign up to set email alerts
|

JTE-522-induced apoptosis in human gastric adenocarinoma cell line AGS cells by caspase activation accompanying cytochrome C release, membrane translocation of Bax and loss of mitochondrial membrane potential

Abstract: AIM:To investigate the role of the mitochondrial pathway in JTE-522-induced apoptosis and to investigate the relationship between cytochrome C release, caspase activity and loss of mitochondrial membrane potential ( Ψ Ψ Ψ Ψ Ψm). METHODS:Cell culture, cell counting, ELISA assay, TUNEL, flow cymetry, Western blot and fluorometric assay were employed to investigate the effect of JTE-522 on cell proliferation and apoptosis in AGS cells and related molecular mechanism.RESULTS: JTE-522 inhibited the growth of AGS ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The descent of rhodamine can reflect the collapse of ΔΨm [16] . In order to determine the effect of PE on ΔΨm, the uptake of rhodamine was detected by flow cytometry.…”
Section: Effect Of Pe On δψM Of Hepg2 Cellsmentioning
confidence: 99%
“…The descent of rhodamine can reflect the collapse of ΔΨm [16] . In order to determine the effect of PE on ΔΨm, the uptake of rhodamine was detected by flow cytometry.…”
Section: Effect Of Pe On δψM Of Hepg2 Cellsmentioning
confidence: 99%
“…After 24 hours, supernatant of the wells was removed, their cells were washed twice with PBS and resuspended by adding trypsin /EDTA (Gibco, Glasgow, UK). [ 20 21 ] After centrifugation, the pellet cells were resuspended in 1 ml of HPSS salt solution and its volume was increased to 10 ml with 70% ethanol. The suspension was maintained at –20° C till the time of evaluating experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental have indicated that pre-exposure of MCF-7 breast cancer cells to paclitaxel followed by 5-FU was preferable [5] . During the last 20 years, accumulating data have shown an anti-proliferative effect of non-steroidal anti-inflammatory drugs (NSAIDs) in a variety of malignant cell lines [6][7][8][9][10][11][12] . PGs and their synthesizing enzyme COX-2 was suggested to be involved in carcinogenesis [13] .…”
Section: Introductionmentioning
confidence: 99%